Implementable Approach of Addressing the Challenges of Cloud Based Smart City Using IoT - Ganesh, E.N (Review of Energy Technologies and Policy Research, 2017)
Implementation of IOT in smart city is a complex issue which requires advanced networking and communication technology and specifically cloud based technology is required. In this paper we introduce the general notion of IoT hubs and then Propose a algorithm to address the challenges faced to implement cloud based SMART Cities. We addressed two issues, one with integration of public and private cloud and another one ability to handle and exchange the data easily. This paper briefly describes an approach to address these issues and discuss about deploying cloud-based Smart City hubs.